Exploring how accessible cultural practices impact on community development: The case of InclusivOpera at the Macerata Opera Festival in Italy. Issue 1 (2nd January 2022) - Giovanni, Elena Di; Luchetti, Marco; Turrini, Alex; Raffi, Francesca
ABSTRACT: The growing importance of inclusion for community development cannot be overcome, especially in areas characterized by cultural clashes, economic disparity, and urban marginalization. In this perspective improving community exposure to the arts and extending the access to cultural programs might play an important role. Arts accessibility might magnify important impacts on the community such as the (re)interpretation of the value of diversity, the enhancement of individual capacities through creativity, the empowerment of citizens' political and democratic participation, and the reinforcement of the sense of belonging of a community. On these grounds, the aim of our article is to describe and discuss what arts accessibility is and how the adoption of inclusive practices by arts institutions might improve community development programs. We also present a case study, the InclusivOpera project at the Macerata Opera Festival (MOF) in Italy, which stands as a critical case to understand how arts accessibility might trigger community development processes.